Improved performance and crystallization behaviors of bimodal HDPE/UHMWPE blends assisted by ultrasonic oscillations. (12th December 2018) - Pan, Xuefeng; Huang, Yu; Zhang, Yan; Liu, Boping; He, Xuelian
Abstract: Blends of a bimodal HDPE, a commercial PE-100 pipe resin and an UHMWPE were prepared in a twin screw extruder assisted by an ultrasound transmitter with a frequency of 20 kHz. The effects of ultrasound on the crystallization behavior, orientation and mechanical properties of the blends were investigated. The results from SEM and TEM revealed that the 600 W ultrasound treatment could improve the dispersion of the UHMWPE in the HDPE matrix and both the ultrasound treatment and the introduction of only 3 wt% UHMWPE could enhance the formation of large size oriented shish-kebab structures. DSC measurements suggested that the crystallization rate of the blends with the introduction of the UHMWPE was increased and more stable nuclei structure as well as thicker crystal lamellae formed with the increase of ultrasonic intensity. POM photos and XRD curves indicated that the introduction of UHMWPE resulted in the formation of small size concentrated nuclei in the blends. Furthermore, the tensile and creep measurement results indicated that the ultrasound treatment, together with the addition of UHMWPE, could slightly improve the tensile properties and creep resistance of both pure HDPE and the blends materials. A conceptual model is presented that qualitatively explained the evolution of the shish-kebab structures during the injection process under the ultrasound treatment.